Research of Finite Element Analysis Method of Gear with Load Shaft and the Application - He Rong; Xu Jin; Zhang Yudong; Li Hongwu; Cheng Yan; Li liang (Jixie chuandong)
In order to calculate the bending stress of the gear accurately,a finite element analysis method of gear with load shaft is proposed based on the three-dimensional accurate modeling. The position of the single-tooth meshing point and the load angle are calculated. The load shaft is mounted contact with the gear.By comparing with the traditional calculation method of the tooth root stress,the correctness of the finite element analysis method of gear with load shaft is demonstrated. The results show that the thickness of the rim has no effect on the tooth root stress by calculating the spur gear with the finite element method,and the limitation of the finite element methods is put forward.